Virosome, a hybrid vehicle for efficient and safe drug delivery and its emerging application in cancer treatment - Liu Hanqing; Tu Zhigang; Feng Fan; Shi Haifeng; Chen Keping; Xu Ximing (Acta Pharmaceutica)
A virosome is an innovative hybrid drug delivery system with advantages of both viral and non-viral vectors. Studies have shown that a virosome can carry various biologically active molecules, such as nucleic acids, peptides, proteins and small organic molecules. Targeted drug delivery using virosome-based systems can be achieved through surface modifications of virosomes. A number of virosome- -based prophylactic and therapeutic products with high safety profiles are currently available in the market. Cancer treatment is a big battlefield for virosome-based drug delivery systems. This review provides an overview of the general concept, preparation procedures, working mechanisms, preclinical studies and clinical applications of virosomes in cancer treatment.